The effect of acute aerobic exercise intensity on indices of blood flow to metastatic liver tumours using non-invasive imaging: a preliminary study - Catherine Seet-Lee; Jasmine Yee; Jillian L. Clarke; Thomas Chalmers Braithwaite; Kate M. Edwards (European Journal of Applied Physiology, 2026)

Patterns of coral spawning in the Palm Islands, Great Barrier Reef - Hanaka Mera; Alasdair J. Edwards; James R. Guest; Liam Lachs; Kate M. Quigley; Bette L. Willis; Andrew H. Baird (Coral Reefs, 2025)
Scleractinian reproductive biology has been a focus of research since the discovery of multi-species synchronous spawning in the early 1980s; however, predicting when colonies will spawn on the Great Barrier Reef remains problematic. Here, we combine over 30 years of direct coral spawning observations that include colonies from 128 species from 44 genera in 10 families with 20 years of data on the stage of gamete maturity in colonies of Acropora (hereafter, colony reproductive condition) from the Palm Island group on the Great Barrier Reef to explore patterns within and among species. We find the lunar month counted from the southern hemisphere winter solstice better predicts the first month of spawning in the Palm Islands than the Gregorian month: spawning was never observed before the 5th lunar month. Direct observations suggest that most coral spawning in the Palm Islands occurs in the 5th and 6th lunar months over a 12-day interval starting one day before the full moon, between 30 min before and 5 h after sunset. Split spawning was also a frequent occurrence in Acropora populations. Some Acropora spp. had colonies that spawned in four or five different lunar months, a pattern that might be affected by taxonomic uncertainty. The range in spawning start times was considerably greater among colonies maintained in the laboratory vs those in the field, suggesting that spawning times are affected by handling. This work highlights the importance of a systematic approach to documenting spawning times to improve our understanding of spawning synchrony and seasonality.

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Saltwater intrusion and sea level rise threatens U.S. rural coastal landscapes and communities - Kiera L. O’Donnell; Emily S. Bernhardt; Xi Yang; Ryan E. Emanuel; Marcelo Ardón; Manuel T. Lerdau; Alex K. Manda; Anna E. Braswell; Todd K. BenDor; Eric C. Edwards; Elizabeth Frankenberg; Ashley M. Helton; et al. (Anthropocene, 2024)

Total infectome investigation of diphtheritic stomatitis in yellow-eyed penguins (Megadyptes antipodes) reveals a novel and abundant megrivirus - Janelle R. Wierenga; Rebecca M. Grimwood; Harry S. Taylor; Stuart Hunter; Lisa S. Argilla; Trudi Webster; Lauren Lim; Rebecca French; Hendrik Schultz; Fátima Jorge; Mihnea Bostina; Laura Burga; et al. (Veterinary Microbiology, 2023)

Aquatic insect accumulation of uranium at spring outflows in the Grand Canyon region as influenced by aqueous and sediment geochemistry and biological factors: implications for monitoring - Daniel J. Cain; Marie-Noële Croteau; Christopher C. Fuller; Kimberly R. Beisner; Kate M. Campbell; Deborah L. Stoliker; Edward R. Schenk (Environmental Monitoring and Assessment, 2023)

Correction to: Partial body cryotherapy exposure drives acute redistribution of circulating lymphocytes: preliminary findings - Catriona L. Rose; Helen McGuire; Kenneth Graham; Jason Siegler; Barbara Fazekas de St Groth; Corinne Caillaud; Kate M. Edwards (European Journal of Applied Physiology, 2023)

Partial body cryotherapy exposure drives acute redistribution of circulating lymphocytes: preliminary findings - Catriona L. Rose; Helen McGuire; Kenneth Graham; Jason Siegler; Barbara Fazekas de St Groth; Corinne Caillaud; Kate M. Edwards (European Journal of Applied Physiology, 2023)
Partial body cryotherapy (PBC) is proposed to alleviate symptoms of exercise-induced muscle damage (EIMD) by reducing associated inflammation. No studies have assessed acute PBC exposure on peripheral blood mononuclear cell mobilisation or compared these with cold water immersion (CWI), which may inform how PBC impacts inflammatory processes. This trial examined the impact of a single PBC exposure on circulating peripheral blood mononuclear cells compared to CWI or a control. 26 males were randomised into either PBC (3 min at − 110 to − 140 °C), CWI (3 min at 9 °C), or control (3 min at 24 °C), with blood samples, heart rate, and blood pressure taken before and after exposure. Cytometric analysis determined that CD8 + T-cell populations were significantly elevated after treatments, with PBC increasing CD8 + T cells to a greater degree than either CWI or CON. Natural killer cell counts were also elevated after PBC, with the increase attributed specifically to the CD56 lo CD16 + cytotoxic subset. This provides the first evidence for the effect of PBC exposure on redistribution of immune cells. An increase in circulating leukocyte subsets such as CD8 + T cells and CD56 lo CD16 + natural killer cells suggests that PBC may induce a transient mobilisation of lymphocytes. PBC may thus enable a more efficient trafficking of these cells from the circulation to the site of initial cellular insult from exercise, potentially accelerating the process of cellular recovery. This provides novel evidence on the use of PBC as a recovery treatment and may also have applicability in other clinical settings involving the recovery of damaged skeletal muscle.

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Antarctic desert soil bacteria exhibit high novel natural product potential, evaluated through long‐read genome sequencing and comparative genomics - Nicole Benaud; Richard J. Edwards; Timothy G. Amos; Paul M. D'Agostino; Carolina Gutiérrez‐Chávez; Kate Montgomery; Iskra Nicetic; Belinda C. Ferrari (Environmental Microbiology, 2021)
Summary Actinobacteria and Proteobacteria are important producers of bioactive natural products (NP), and these phyla dominate in the arid soils of Antarctica, where metabolic adaptations influence survival under harsh conditions. Biosynthetic gene clusters (BGCs) which encode NPs, are typically long and repetitious high G + C regions difficult to sequence with short‐read technologies. We sequenced 17 Antarctic soil bacteria from multi‐genome libraries, employing the long‐read PacBio platform, to optimize capture of BGCs and to facilitate a comprehensive analysis of their NP capacity. We report 13 complete bacterial genomes of high quality and contiguity, representing 10 different cold‐adapted genera including novel species. Antarctic BGCs exhibited low similarity to known compound BGCs (av. 31%), with an abundance of terpene, non‐ribosomal peptide and polyketide‐encoding clusters. Comparative genome analysis was used to map BGC variation between closely related strains from geographically distant environments. Results showed the greatest biosynthetic differences to be in a psychrotolerant Streptomyces strain, as well as a rare Actinobacteria genus, Kribbella , while two other Streptomyces spp. were surprisingly similar to known genomes. Streptomyces and Kribbella BGCs were predicted to encode antitumour, antifungal, antibacterial and biosurfactant‐like compounds, and the synthesis of NPs with antibacterial, antifungal and surfactant properties was confirmed through bioactivity assays.

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.

Decrease in 230 Th in the Amundsen Basin since 2007: far-field effect of increased scavenging on the shelf? - Ole Valk; Michiel M. Rutgers van der Loeff; Walter Geibert; Sandra Gdaniec; S. Bradley Moran; Kate Lepore; Robert Lawrence Edwards; Yanbin Lu; Viena Puigcorbé; Nuria Casacuberta; Ronja Paffrath; William Smethie; et al. (Ocean Science, 2020)
This study provides dissolved and particulate 230Th and 232Th results as well as particulate 234Th data collected during expeditions to the central Arctic Ocean (GEOTRACES, an international project to identify processes and quantify fluxes that control the distributions of trace elements; sections GN04 and GIPY11). Constructing a time series of dissolved 230Th from 1991 to 2015 enables the identification of processes that control the temporal development of 230Th distributions in the Amundsen Basin. After 2007, 230Th concentrations decreased significantly over the entire water column, particularly between 300 and 1500 m. This decrease is accompanied by a circulation change, evidenced by a concomitant increase in salinity. A potentially increased inflow of water of Atlantic origin with low dissolved 230Th concentrations leads to the observed depletion in dissolved 230Th in the central Arctic. Because atmospherically derived tracers (chlorofluorocarbon (CFC), sulfur hexafluoride (SF6)) do not reveal an increase in ventilation rate, it is suggested that these interior waters have undergone enhanced scavenging of Th during transit from Fram Strait and the Barents Sea to the central Amundsen Basin. The 230Th depletion propagates downward in the water column by settling particles and reversible scavenging.

3D Printing of Calcium Phosphate Ceramics for Bone Tissue Engineering and Drug Delivery - Ryan Trombetta; Jason A. Inzana; Edward M. Schwarz; Stephen L. Kates; Hani A. Awad (Annals of Biomedical Engineering, 2017)

The effects of 24 weeks of moderate- or high-intensity exercise on insulin resistance - Gary O’Donovan; Edward M. Kearney; Alan M. Nevill; Kate Woolf-May; Steve R. Bird (European Journal of Applied Physiology, 2005)